Twisted fate : a novel - Olson, Norah (2015)
Told from separate viewpoints, unfolds how sisters Sydney and Ally Tate's relationship changes as they get involved with their new neighbor, Graham, an artist with a videocamera who has a mysterious--and dangerous--past.
Keywords: Mental illness -- Juvenile fiction; Sisters -- Juvenile fiction; Neighbors -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Artists -- Juvenile fiction; Mental illness -- Fiction; Sisters -- Fiction; Neighbors -- Fiction; High schools -- Fiction; Schools -- Fiction; Artists -- Fiction; Young adult fiction